2023
DOI: 10.1167/iovs.64.6.6
|View full text |Cite
|
Sign up to set email alerts
|

IMI—Global Trends in Myopia Management Attitudes and Strategies in Clinical Practice—2022 Update

Abstract: Purpose Surveys in 2015 and 2019 identified a high level of eye care practitioner concern/activity about myopia, but the majority still prescribed single vision interventions to young myopes. This research aimed to provide updated information. Methods A self-administered, internet-based questionnaire was distributed in 13 languages, through professional bodies to eye care practitioners globally. The questions examined awareness of increasing myopia prevalence, perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…Despite its extensive use in numerous clinical trials (Supplementary Table 3 ), no systemic adverse effects have been reported [ 19 ]. However, both the effect and safety of atropine remain controversial, which likely has led to differing opinions on its use [ 66 , 121 , 126 ]. In regions where atropine is relatively widely used to control myopia progression in children, studies are being conducted to investigate its use for preventing myopia onset in premyopic children and have shown positive results [ 109 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite its extensive use in numerous clinical trials (Supplementary Table 3 ), no systemic adverse effects have been reported [ 19 ]. However, both the effect and safety of atropine remain controversial, which likely has led to differing opinions on its use [ 66 , 121 , 126 ]. In regions where atropine is relatively widely used to control myopia progression in children, studies are being conducted to investigate its use for preventing myopia onset in premyopic children and have shown positive results [ 109 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies in diverse populations including clinical trials and real-world settings are necessary to confirm and validate the effectiveness of these newer optical interventions. Overall, these spectacles are gaining more and more popularity [ 66 ], because they seem safe, they do not create visual distortion, and above all their appearance is similar to SVL spectacles. Compared to SVL spectacles, however, these myopia control spectacles are significantly more expensive and not accessible to everyone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations